(untitled) (TAMADDUN NURI JURNALI, 2024)
The article examines the main functions of borrowed words in the speech of older people. The research material includes videos from the website www.youtube.com, which demonstrate the speech of older people. It has been established that the use of borrowed words in the speech of older people can be due to several reasons.